Snail species of Viviparidae in Vietnam - Thanh, Dang Ngoc; Hai, Ho Thanh; Cuong, Duong Ngoc (Academia Journal of Biology, 2015)
Based on analysing snail samples of Viviparidae collected from 1975 (maily in southern part of Vietnam) at the same time with revision on taxonomy of this family, research results show that this snail of Viviparidae has 9 species belong to 5 gennera in Vietnam: Cipangopaludina lecythoides (Benson, 1856); Idiopoma umbilicata (Lea, 1856); Filopaludina sumatrensis (Dunker, 1852); Sinotaia aeruginosa (Reeve, 1863); Angulyagra polyzonata (Frauenfeld, 1862); Angulyagra duchieri (Fischer, 1908); Angulyagra boettgeri (Heude, 1890); Mekongia hainesiana (Lea, 1957); and Mekongia lithophaga (Heude, 1889). The key of identifation for snail of Viviparidae in Vietnam and some remarkes on taxonomic position of some species such as C. leycithoides, I. Umblicata, F. sumatrensis as well as species group of gennera: Angulyagra, Sinotaia those that are given also in this paper.